Prevalence of Bullying Behaviors Among Students From a National University in the United Arab Emirates: A Cross-Sectional Study - Al-Darmaki, Fatima; Al Sabbah, Haleama; Haroun, Dalia (Frontiers in Psychology, 2022)
Background: This cross-sectional study aims to investigate bullying behaviors among college students at one of the national universities in UAE, and also to examine the psychological characteristics of those who were exposed to, or have experienced bullying. Methods: Eight hundred and thirty nine undergraduate students participated in the study by filling out a bullying survey designed for the study, in addition to three psychological measures (i.e., Aggression Questionnaire, Buss &Perry,1992; The Primary Care Anxiety and Depression, El-Rufaie et al., 1997; and the Post Traumatic Stress Disorder (PTSD) for Diagnostic and Statistical Manual of Mental Disorders- Fifth Edition (PCL-5), Weathers et al, 2013). Results: The prevalence rate of students being exposed to or engaged in bullying was 26.3% (221 out of 839). Of those, 72 students (8.7%) reported being bullied, 29 (3.6%) reported bullying others, and 185 (22.8%) reported witnessing friends being bullied. The most common types of bullying reported were traditional bullying (e.g., face to face bullying, verbal, physical). Cyberbullying was not very common. More females reported being bullied in comparison to males and most of the aggressors were peer students. Overall, moderate level of aggressive personality traits and low levels of symptoms of depression, anxiety, and PTSD were reported for the total sample. T-tests revealed significant differences in the three psychological measures between those who did not experience bullying and those who did. The mean scores on the Aggression Questionnaire for those who bullied others, were significantly higher than those who did not experience bullying. Conclusions: Experiences of bullying seem to impact college students’ mental health in the UAE. Therefore, efforts need to focus on developing preventive programs to increase students’ awareness of bullying and its negative impact on campus environment. Offering psychological help for those who were exposed to bullying would help them to deal effectively with this trauma.